A Probable Reason for Qur’ānic Prohibition of Ribā: Dissimilarity of Price and Interest Rate as Equilibrating Variables - Iqbal, Muhammad Mazhar; Shah, Anwar (Islamic Studies, 2024)
The Qur’ān bans interest (ribā) and declares its dissimilarity with price in commodity trading. This paper provides a numerical explanation for this dissimilarity. It argues that calculating accrued interest for any loan requires information about the interest rate and compounding period. The compounding period is generally not stated explicitly; rather, it is inferred from the repayment schedule of a loan and bond. For a given principal and interest rate, the interest amount changes in response to any change in the compounding period. Alternatively, for any timeline to repay a prescribed amount of loan more than once a year, three different rates are defined. These are nominal interest rate, internal rate of return, and annual percentage rate. Since various participants in the loanable funds market concentrate on different rates and the ranking of alternative loan options concerning these rates may be contradictory, the law of one interest rate with respect to any one of these three rates is highly implausible if not impossible to prevail in the loanable funds market.